2018
DOI: 10.3389/fimmu.2018.02918
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome: A Possible Link Between Obesity-Associated Low-Grade Chronic Inflammation and Colorectal Cancer Development

Abstract: Emerging evidence reveals that adipose tissue-associated inflammation is a main mechanism whereby obesity promotes colorectal cancer risk and progression. Increased inflammasome activity in adipose tissue has been proposed as an important mediator of obesity-induced inflammation and insulin resistance development. Chronic inflammation in tumor microenvironments has a great impact on tumor development and immunity, representing a key factor in the response to therapy. In this context, the inflammasomes, main co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 218 publications
0
76
0
6
Order By: Relevance
“…Although various mechanisms, such as chronic inflammation, sex hormone deregulation, and adipokine pathophysiology, have been proposed for the linkage between adiposity and cancer [51,52], the underlying molecular mechanisms still remain poorly understood. Emerging evidence also reveals that adipose tissue-associated inflammation is a major mechanism by which obesity promotes metabolic disorders and cancer risk [53,54]. Therefore, the role of inflammasomes, a key player in inflammatory and immune responses, in regard to obesity-related diseases, has been being paid increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…Although various mechanisms, such as chronic inflammation, sex hormone deregulation, and adipokine pathophysiology, have been proposed for the linkage between adiposity and cancer [51,52], the underlying molecular mechanisms still remain poorly understood. Emerging evidence also reveals that adipose tissue-associated inflammation is a major mechanism by which obesity promotes metabolic disorders and cancer risk [53,54]. Therefore, the role of inflammasomes, a key player in inflammatory and immune responses, in regard to obesity-related diseases, has been being paid increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…Rat studies indicate that long-term intake of a high-fat diet (HFD) can lead to impaired lipid metabolism, as indicated by elevated total cholesterol (TC), triglyceride (TG), and low-density lipoprotein (LDL) levels [4]. In addition to the disruption of lipid metabolism, low-grade chronic inflammation has been identified as a potential mechanism of obesity-related conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the aberrant expression of NALP3 may result in severe intestinal inflammation, triggering the cyclical activation of the NALP3 inflammasome [ 8 ]. IL-1β and IL-18, the downstream signaling molecules from the NLRP3 pathway, have pleiotropic effects on CRC tumorigenesis [ 9 , 10 , 11 , 12 ]. Studies have indicated elevated expression of NALP3 inflammasome in CRC tumour tissue samples [ 13 , 14 , 15 , 16 ], and a positive correlation has been defined between NALP3 and distance metastasis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated elevated expression of NALP3 inflammasome in CRC tumour tissue samples [ 13 , 14 , 15 , 16 ], and a positive correlation has been defined between NALP3 and distance metastasis [ 16 ]. However, several studies have also reported the effects of the low levels of the NALP3 inflammasome function on CRC development [ 17 , 18 ], which suggests that NALP3 inflammasome plays a balancing role in the regulation of inflammation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%